Casposon integration shows strong target site preference and recapitulates protospacer integration by CRISPR-Cas systems. Issue 21 (20th September 2016) - Béguin, Pierre; Charpin, Nicole; Koonin, Eugene V.; Forterre, Patrick; Krupovic, Mart
Abstract: Casposons are a recently discovered group of large DNA transposons present in diverse bacterial and archaeal genomes. For integration into the host chromosome, casposons employ an endonuclease that is homologous to the Cas1 protein involved in protospacer integration by the CRISPR-Cas adaptive immune system. Here we describe the site-preference of integration by the Cas1 integrase (casposase) encoded by the casposon of the archaeon Aciduliprofundum boonei . Oligonucleotide duplexes derived from the terminal inverted repeats (TIR) of the A. boonei casposon as well as mini-casposons flanked by the TIR inserted preferentially at a site reconstituting the original A. boonei target site. As in the A. boonei genome, the insertion was accompanied by a 15-bp direct target site duplication (TSD). The minimal functional target consisted of the 15-bp TSD segment and the adjacent 18-bp sequence which comprises the 3΄ end of the tRNA-Pro gene corresponding to the TΨC loop. The functional casposase target site bears clear resemblance to the leader sequence-repeat junction which is the target for protospacer integration catalyzed by the Cas1–Cas2 adaptation module of CRISPR-Cas. These findings reinforce the mechanistic similarities and evolutionary connection between the casposons and the adaptation module of the prokaryotic adaptive immunity systems.